Growth and instability in dairy production and trade: a global analysis. (26th June 2014) - Ohlan, Ramphul
The study investigates the pattern of growth and instability in the production and trade of dairy products at the global level and in the world leading producers, exporters and importers in the context of the World Trade Organization (WTO) regime using the log linear regression model, decomposition analysis and standard deviation of growth rate. The basic characteristics of the dairy industry in the world leading exporters of dairy products are briefly reviewed. We find that under the WTO regime for the world at large and in most of the leading producers, the growth rate of milk production has increased statistically significantly while its instability has declined. It indicates that high rate of growth in milk production does not cause high instability. Our findings suggest that there is a need for enhancing the domestic dairy production by focusing on improvements in yield and encouraging the processing of milk to meet the fast–growing demand for a large lacto–vegetarian populated country like India.